Entomopathogenic fungi associated with the main insect pest in the Northeast of Portugal: preliminary results - Baptista, Paula (2011)
Due to the problems caused by the use of chemical insecticides for humans and environment alternative pest control methods are an important topic of research. The use of microbial insecticides especially fungal agents are an attractive and promising alternative for biological control of insect pests. The aim of this work was to identify naturally occurring entomophatogenic fungi on the olive moth, Prays oleae Bern., in the northeast of Portugal, as first step to select biological control agent again this olive pest. The experimental work was carried out during 2007 in the three generation of the insect (phyllophagous, anthophagous and carpophagous generation). In each generation P. oleae larvae and pupae were collected in different groves and were put in glass vials in a climatic chamber with a photoperiod of 12h light:12h dark, 22ºC (light): 16ºC (dark) and 60% relative humidity, until emergency of the adults. From dead larvae, fungi were isolated on PDA plates and incubated at room temperature. Pure cultures were morphological and molecularly identified based on the ITS region of the rDNA. From the identified species Beauveria bassiana Vuill. and Cordyceps sinensis (Berk.) Sacc. were the most promising being B. bassiana the most abundant one.